2019
DOI: 10.1016/j.erss.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

‘Doing good science’: The impact of invisible energy policies on laboratory energy demand in higher education

Abstract: Education is the second largest consumer of energy in the service sector, however, little research to date has focused on the link between education policy and energy demand. Using a case study, this paper explores the role of invisible energy policies in Higher Education (HE). We make a distinctive contribution to debates about invisible energy policy by applying concepts from governmentality to show how different policies and technologies of governance come in to conflict in practice. And, we argue that alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Khoshbakht et al [9] investigated 80 university buildings in Australia and found that research buildings have the highest energy use intensity (EUI) while academic offices had the lowest EUI. These findings have been upheld by other studies in Australia [7] , the UK [10] , [11] and China [8] . The high EUI of research spaces might result from the long working hours [8] even during holidays [7] .…”
Section: Introductionmentioning
confidence: 80%
“…Khoshbakht et al [9] investigated 80 university buildings in Australia and found that research buildings have the highest energy use intensity (EUI) while academic offices had the lowest EUI. These findings have been upheld by other studies in Australia [7] , the UK [10] , [11] and China [8] . The high EUI of research spaces might result from the long working hours [8] even during holidays [7] .…”
Section: Introductionmentioning
confidence: 80%
“…Additionally, Participants 8 and 13 emphasised that Cardiff University is a researchintensive institution requiring a lot of equipment, which is not necessarily 'good' for the environment but is nevertheless seen as essential for research activities. The 20 research-intensive institutions that belong to the Russell Group collectively contribute to over half of the UK's university carbon emissions (Gormally et al, 2019). Being a Russell Group member, Cardiff University has departments whose research requires energy-consuming scienti c equipment.…”
Section: Implementing Sustainable Practicementioning
confidence: 99%
“…These dialogues assert that Cardiff University could be seeking alternative technologies that will have less impact on the environment. Yet, often 'doing the science' overrules energy-related decisions (Gormally et al, 2019), suggesting that research excellence competes with sustainability in the higher-education context and potentially challenges the role of universities as leaders in this eld.…”
Section: Participant 8 Concurredmentioning
confidence: 99%
“…This echoes discourses about individualised responsibility for addressing global environmental crises, which have been widely debated elsewhere (for example, by Walker, 2015). As Gormally, O'Neill, Hazas, Bates, and Friday (2019) suggest, neoliberal narratives can have a powerful effect in steering how university researchers use energy; such narratives may also affect how energy management is understood by EMPs across sectors, and how they and their institutions understand the limits of legitimate intervention. Of course, these effects are not static.…”
Section: How and Why Do These Patterns Of Marginalisation Emerge?mentioning
confidence: 99%